2013
DOI: 10.1111/aji.12089
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pregnancy‐Specific Glycoprotein 1a (PSG1a) in Regulating the Innate and Adaptive Immune Response

Abstract: CitationMartinez FF, Cervi L, Knubel CP, PanzettaDutari GM, Motran CC. The role of pregnancyspecific glycoprotein 1a (PSG1a) in regulating the innate and adaptive immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 123 publications
2
25
0
1
Order By: Relevance
“…The 111 up-regulated genes included multiple transcripts involved in immune activation ( CXCL14, CCL13, IL2B , SPP1 , STAT4, TNFRSF21 , TNFSF10 ), prostaglandin synthesis ( PTGES, PTGDS ), and tissue remodeling ( COL1A1 , COL1A2 , COL5A1 COL5A2 , KRT6A, KRT6C, KRT24, KRT7). Prominent among the 233 transcripts down-regulated with disadvantage were pregnancy-specific glycoproteins ( PSG5 , PSG7 , PSG11 ) and the chorionic gonadotropin beta/luteinizing hormone beta gene cluster ( CGB , CGB1 , CGB5 , CGB7 , CGB8, LGB ), which all have roles in fetal immune tolerance (Martinez et al 2013; Bansal et al 2012). Other down-regulated transcripts included suppressors of cytokine signaling ( SOCS2, A2M, PIK3AP1 ), and inhibitors of histamine and prostaglandin activity ( PGT , ABP1 ), as well as mediators of fetal nutrient access, blood supply, and organ maturation ( CGB , CGB1 , CGB5 , CGB8 , MMP12 ), and transcripts found to be hypermethylated in association with nutrient deficiency ( MEG3 , PEG10, SLC38A2 , and LEP ) (Tobi et al 2015).…”
Section: Study 1 Resultsmentioning
confidence: 99%
“…The 111 up-regulated genes included multiple transcripts involved in immune activation ( CXCL14, CCL13, IL2B , SPP1 , STAT4, TNFRSF21 , TNFSF10 ), prostaglandin synthesis ( PTGES, PTGDS ), and tissue remodeling ( COL1A1 , COL1A2 , COL5A1 COL5A2 , KRT6A, KRT6C, KRT24, KRT7). Prominent among the 233 transcripts down-regulated with disadvantage were pregnancy-specific glycoproteins ( PSG5 , PSG7 , PSG11 ) and the chorionic gonadotropin beta/luteinizing hormone beta gene cluster ( CGB , CGB1 , CGB5 , CGB7 , CGB8, LGB ), which all have roles in fetal immune tolerance (Martinez et al 2013; Bansal et al 2012). Other down-regulated transcripts included suppressors of cytokine signaling ( SOCS2, A2M, PIK3AP1 ), and inhibitors of histamine and prostaglandin activity ( PGT , ABP1 ), as well as mediators of fetal nutrient access, blood supply, and organ maturation ( CGB , CGB1 , CGB5 , CGB8 , MMP12 ), and transcripts found to be hypermethylated in association with nutrient deficiency ( MEG3 , PEG10, SLC38A2 , and LEP ) (Tobi et al 2015).…”
Section: Study 1 Resultsmentioning
confidence: 99%
“…In addition, interesting proteins such as Ficolin 3 and pregnancy-specific beta-1-glycoprotein 4 participated in innate immunity were firstly identified down-regulated in GDM plasma. Human pregnancy-specific beta-1-glycoproteins (PSGs), a representative member of the main glycoprotein family secreted by placental trophoblast, may modulate the activation of antigen-presenting cells promoting the T-cell shift of the maternal cell immunity toward a less harmful phenotype [36]. Previous studies have reported abnormal levels of PSGs in complicated pregnancies and have shown their importance for the maintenance of a successful pregnancy [37].…”
Section: Discussionmentioning
confidence: 99%
“…The actions of PSG1 on cells of the innate and adaptive immune system have been recently reviewed in (Martinez et al, 2013). IL-10 and TGF-b are suppressor cytokines, which are interrelated (Kitani et al, 2003, Li et al, 2006, Moore et al, 2001.…”
Section: Pregnancy-specific Glycoproteins 277mentioning
confidence: 99%